Investigation of Therapeutic and Protective Action of Reaferon-ES Lipint® on Mice Infected with Avian Influenza Virus (Subtype H5N1) - O. K. Demina; A. A. Sergeev; A. P. Agafonov; A. N. Shikov; A. O. Sementsova; AL. A. Sergeev; A. N. Sergeev; I. G. Drozdov (Антибиотики и Химиотерапия)
The efficacy of the therapeutic, prophylactic and urgent prophylactic schemes for the use of Reaferon-ES lipint®, a liposomal human recombinant α-interferon for oral use, was studied on mice infected with the avian influenza virus. Strain A/Chicken/Kurgan /05/2005 (subtype H5N1) of the avian influenza virus showed high virulence with respect to mice ICR. Theoretically-based calculations allowed to design an optimal therapeutic and prophylactic dose of the drug for the mice (1000 units/animal). It was observed that only after prophylactic use of Reaferon-ES lipint® it was effective in protection of the mice infected with 10 LD50 of the avian influenza virus (A/Chicken/Kurgan/05/2005, H5N1). The protection coefficient was 0.35. Under such conditions the drug efficacy was comparable with that of Tamiflu. Therefore, Reaferon-ES lipint® could be recommended for prophylaxis of the infection due not only to the season strains of the influenza virus, but also to the strains of the avian influenza virus.